Isolated avulsion fracture of the fibular head - Harhaji, Vladimir V; Lalić, Ivica; Vranješ, Miodrag; Mikić, Milena; Djan, Vladimir (Vojnosanitetski pregled, 2021)
Introduction. Rupture of lateral collateral ligament of the knee is most often joined with other ligament ruptures. Isolated rupture of this ligament is rare and there are few papers about treatment options and results. Here we reported a case of isolated lateral collateral ligament rupture and the treatment outcome. Case report. A patient, 22 years old male, injured his left knee while playing American football. While landing on the outstretched left leg, he felt a sudden pain in his knee. The patient could not continue the competition. Initial orthopedic examination revealed lateral opening and further diagnostic procedure (magnetic resonance imaging) revealed isolated grade III rupture of lateral collateral ligament with avulsion fracture of the fibular head, and distension of anterior and posterior cruciate ligaments. Patient was surgically treated with metal sutures passed through conjoined tendon and proximal fibula. Postoperatively patient worn above knee cast for 6 weeks and after that he was included in rehabilitation. Three and six years after this injury, the patient has still been professional football player with no symptoms and no clinical instability of the knee despite radiological and computed tomography verified pseudoarthrosis of the fractured fibular head fragment. Conclusion. Early diagnostic and absence of additional injuries of the knee leads to a faster and full functional recovery of patients with isolated avulsion fracture of the fibular head, while surgical treatment provides knee stability with no residual ligament instability during sports activities.